2022
DOI: 10.32479/ijeep.12670
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth, Financial Development, Energy Consumption and Life Expectancy: Fresh Evidence from ASEAN countries

Abstract: The study examines the relationship between economic growth and life expectancy by considering the potential role of financial development and energy consumption in ASEAN Countries. Unit root testing was applied to check the level stationarity data before checking for cointegration between variables using the Error Correction Term (ECT) approach, and ARDL bounds testing was applied for cointegration with structural damage that occurred at a specific time using the Pooled Mean Group (PMG) and Pooled Mean Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Another possible explanation for this finding is that an increase in ECD means that the income level of citizens will be on the rise; this can provide financial stability and enable people to pay for proper medical care to remedy specific illnesses and prolong lives [ 29 ]. Similar to these results [ 26 ], reported that an improvement in income and ECD is essential in making citizens more health-conscious, influencing their living standards, and ultimately improving their LEX. The finding from this analysis complies with the results from erstwhile studies that revealed that ECD positively impacts LEX [ [25] , [26] , [27] , [28] , 94 ].…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Another possible explanation for this finding is that an increase in ECD means that the income level of citizens will be on the rise; this can provide financial stability and enable people to pay for proper medical care to remedy specific illnesses and prolong lives [ 29 ]. Similar to these results [ 26 ], reported that an improvement in income and ECD is essential in making citizens more health-conscious, influencing their living standards, and ultimately improving their LEX. The finding from this analysis complies with the results from erstwhile studies that revealed that ECD positively impacts LEX [ [25] , [26] , [27] , [28] , 94 ].…”
Section: Resultssupporting
confidence: 77%
“…The indicator for LEX at birth was selected based on the analysis by Refs. [ 5 , 27 , 29 ]; ECD [ [25] , [26] , [27] ]; HUC [ 36 , 49 , 50 ]; AIP [ 10 , 29 , 54 ]; REC [ 31 , 59 , 60 ] and NRR [ 38 , 45 ]. Following these prior studies, equation (1) will be used to determine the function of the antecedents of LEX.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…iii) The results provided by the literature reveal that economic growth improves health status (Sirag et al, 2017;Majeed et al, 2021;Bouchoucha, 2021;Wang et al, 2020a;Azam et al, 2022;Bunyaminu et al, 2022;Hendrawaty et al, 2022;Sial et al, 2022). On the other hand, Ecevit et al (2022) indicate that economic growth negatively affects health outcomes in Turkey.…”
Section: Literaturementioning
confidence: 98%